[Who is nextn ; A question of turf destination ; Camiguin [videorecording] (Quezon City Probe Productions, 1992)
An investigative report on the kidnapping and death of Charlene Sy and the continuous kidnapping of Filipino-Chinese in the country; and the unification of Ayala Stock Exchange and Makati Stock Exchange. Probe visits the volcanic island of Camiguin.
Who is next (19 min.) -- A question of turf destination (15 min.) -- Camiguin (10 min.)
VHS.
Keywords: Kidnapping -- Philippines; Building sites -- Philippines; Stock exchange -- Philippines; Camiguin Island -- Description and travel